3D data acquisition for bioarchaeology, forensic anthropology, and archaeology - Seguchi, Noriko; Dudzik, Beatrix (Academic Press, 2019)
3D Data Acquisition for Bioarchaeology, Forensic Anthropology, and Archaeology serves as a handbook for the collection and processing of 3-D scanned data and as a tool for scholars interested in pursuing research projects with 3-D models. The book's chapters enhance the reader's understanding of the technology by covering virtual model processing protocols, alignment methods, actual data acquisition techniques, basic technological protocols, and considerations of variation in research design associated with biological anthropology and archaeology.